The Profitability Affection on Determinant Factor of Firm Value with Corporate Social Responsibility (CSR) as Moderating - Hardiyanti, Siti Epa (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
The research to analyze the effect of profitability on determination factor of firm value with CSR as moderating variable. The population is all Companies in the Food and Beverage Industry Sub-Sector that are Registered at the IDX for the 2014 - 2021, while the sample is determined by purposive sampling, obtained 35 company. Structural Equation Modeling (SEM) is used to analyze the regression equation model between the data variable. The results of hypothesis testing indicate that firm value can be manifested through optimal management of profitability and Good Corporate Governance (GCG). Profitability can be applied through the size of the company. GCG had direct effect on firm value, while company size had direct affect to profitability. GCG had affect to profitability and a significant direct effect on firm value. CSR as a pure moderator of the effect of profitability on firm value.